Advanced attribute control charts - Zhang, Xiao Lan (2009)
The aim of this research project is to conduct the basic research in computer-aided Statistical Process Control (SPC), in order to improve the performance of conventional attributes control charts monitoring the fraction nonconforming of the process. The project adopts the following techniques: statistical analysis, simulation and optimization.